Sadd Al-Żari'ah Review of Iṡbāt Nikah Sirri at the Syar'iyah Court in Banda Aceh - Nasaiy Aziz; Rafidah Rafidah (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2023)
Iṡbāt nikah is a marriage determination in order to obtain authentic evidence and to obtain protection and legal force, especially for wife and children. The Syar'iyah Court has the authority to receive, examine and adjudicate cases between people who are Muslim. One of them is the application for iṡbāt marriage Number 232/Pdt.P/2022/MS.Bna. However, after being studied and tried, this application was rejected by the panel of judges because it did not meet the requirements for the granting of the marriage iṡbāt. Therefore, the author wants to know what is the basis for the consideration of the panel of judges at the Banda Aceh Syar'iyah Court in rejecting the application for iṡbāt nikah from a sirri marriage in case Number 232/Pdt.P/2022/MS.Bna. And what about sadd al-żari'ah's review of the stipulation and legal basis for the consideration of the panel of judges at the Banda Aceh Syar'iyah Court rejecting the application for iṡbāt nikah from a sirri marriage in case Number 232/Pdt.P/2022/MS.Bna. In this study the authors used a qualitative research method with a normative juridical approach and used a type of library research (Library Research). The results of this study indicate that the panel of judges rejected the application for iṡbāt marriage Number 232/Pdt.P/2022/MS.Bna because the marriage guardian of Petitioner II (wife) is not his biological father or a person who has blood relations with Petitioner II, but tengku who was at the Islamic boarding school where they got married and was also not represented by Petitioner II's biological father to said tengku. Iṡbāt nikah is in accordance with the theory of sadd al-żari'ah. This is necessary to realize benefit and avoid damage.